Driving Factors of Loot Box Impulse Purchases on Indonesian FPS and Moba Generation Z Players - Taufiq, Muhammad Fernanda; Sobari, Nurdin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The transition of the business model from games as a product to games as a service resulted in the birth of the microtransaction business model. In its development, microtransactions have given birth to many products, one of which is loot boxes. As a definition, a loot box is a gift box that can be redeemed to get random items and exclusive products from the game. This research was conducted with the aim of finding out the driving factors for impulsive purchases of loot boxes among Indonesian Generation Z FPS and MOBA video game players. This research is a survey research applied to 300 respondents who have specific criteria in the age range 18-25, especially MOBA and FPS players and have playing experience for one year or more. This research was conducted using the PLS-SEM method using SmartPLS 3.0. The research results show that the factors that influence impulsive loot box purchases and purchase intentions are perceived performance and functional value, self-control depletion, flow of experience, hedonic browsing, and social personalization attributes. It doesn't stop there, it turns out that price also has a moderating effect on intention to buy loot boxes. The price increase for loot boxes is in the range of Rp. 10,000 to Rp. 50,000 indicates a decrease in purchasing intentions based on the results of research that has been carried out.